Adsorption-based atmospheric water harvesting device for arid climates - Kim, Hyunho (Nat Commun, 2018)
Water scarcity is a particularly severe challenge in arid and desert climates. While a substantial amount of water is present in the form of vapour in the atmosphere, harvesting this water by state-of-the-art dewing technology can be extremely energy intensive and impractical, particularly when the relative humidity (RH) is low (i.e., below ~40% RH). In contrast, atmospheric water generators that utilise sorbents enable capture of vapour at low RH conditions and can be driven by the abundant source of solar-thermal energy with higher efficiency. Here, we demonstrate an air-cooled sorbent-based atmospheric water harvesting device using the metal−organic framework (MOF)-801 [Zr(6)O(4)(OH)(4)(fumarate)(6)] operating in an exceptionally arid climate (10–40% RH) and sub-zero dew points (Tempe, Arizona, USA) with a  thermal efficiency (solar input to water conversion) of ~14%. We predict that this device delivered over 0.25 L of water per kg of MOF for a single daily cycle.